2005
DOI: 10.1007/s11274-004-4799-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fluorescent Pseudomonads and Bacillus isolates for the biocontrol of a wilt disease complex of pigeonpea

Abstract: Twenty isolates of fluorescent pseudomonads and Bacillus spp. were obtained from pathogen suppressive soil of a pigeonpea (Cajanus cajan) field showing wilt disease complex. These isolates were evaluated in the laboratory and screen-house for the biocontrol of wilt disease complex. Six isolates were considered to have potential for the biocontrol of the disease on the basis of antibiotic sensitivity, antifungal activity, fluorescence produced by Pseudomonas, inhibitory effect on the hatching and penetration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…Various reports have shown that supplementing the soils with fungal or bacterial antagonists reduces incidences of Fusarium wilt (Bapat and Shar, 2000;Singh et al, 2002;Anjaiah et al, 2003;Maisuria et al, 2008). This also confirms the findings of Bapat and Shar (2000), Siddiqui et al (2005), Siddiqui (2006) and Siddiqui and Shakeel (2007) in which they revealed that numerous rhizobacteria have been used as biocontrol agents. Soil amendment with Trichoderma harzianuma all pathogen levels has also been reported to give a disease control of 22-61.5% (Prasad et al 2002).…”
Section: Effect On Germination Percentsupporting
confidence: 79%
“…Various reports have shown that supplementing the soils with fungal or bacterial antagonists reduces incidences of Fusarium wilt (Bapat and Shar, 2000;Singh et al, 2002;Anjaiah et al, 2003;Maisuria et al, 2008). This also confirms the findings of Bapat and Shar (2000), Siddiqui et al (2005), Siddiqui (2006) and Siddiqui and Shakeel (2007) in which they revealed that numerous rhizobacteria have been used as biocontrol agents. Soil amendment with Trichoderma harzianuma all pathogen levels has also been reported to give a disease control of 22-61.5% (Prasad et al 2002).…”
Section: Effect On Germination Percentsupporting
confidence: 79%
“…Several studies have reported that Bacillus strains can be used as biocontrol agents and plant growth promoting inoculants [1,19,28,36,46]. The antagonistic capabilities of B. licheniformis, B. subtilis, B. pumilis, and B. cereus have been demonstrated by several workers [19,31,42,45]. The highest IAA production was recorded for PB-35 (p < 0.05; 29 ± 0.63 μg ml −1 ) on the 6th day.…”
Section: Discussionmentioning
confidence: 93%
“…Several reports have described Bacillus strains worthy to be used as biocontrol agents for plant diseases (Shoda (Marten et al 2000;Siddiqui et al 2005;Li et al 2007). The correlations amongst the studied species of Bacillus showed that B. subtilis and B. licheniformis are stronger and efficient antagonists than the other species.…”
Section: Discussionmentioning
confidence: 99%